(untitled) (International Journal of Nursing Education, 2025)
Background: Obesity is one of the leading causes of death worldwide. It often begins in childhood although most health effects emerge in adulthood. Child underweight is also a significant issue, especially in low-income and lower-middle-income countries. This study was evaluated the factors that are influencing the Body Mass Index (BMI) in children. Methods: The study was a cross-sectional design including 110 mothers of Grade 1 and 2 elementary school students. Simple randomized sampling method was used to select the participants. Results: The average age of mothers in this study was 35 years old and almost half of them were Burmese race group. There were only 8.2% of mothers who had family meals every day and it was also same result with lunch box preparation. The average knowledge and attitude scores of mothers were 13.73 and 70.42 respectively. There were only 16.4% of children who had more than 60 minutes of physical activity every day. 26.4% of children did not consume fruits while there were 12.7% who did not eat vegetable. 6.5% of children were always having sugared drinks. For water intake, 80% of them were drinking 1 litre of water daily. The average BMI of children was 16.4±1.73 ranging from 13.1 to 19.5. In ordinary logistic regression analysis, lunch box preparation, knowledge of mothers and vegetable consumption of children were in association with BMI of children. Conclusion: The study highlighted the influence of maternal characteristics and also child factors which can influence the BMI of children. Knowledge, lunch box preparation characteristics of mother and vegetable consumption of child were associated with BMI.